Equilibrated charge carrier populations govern steady-state nongeminate recombination in disordered organic solar cells - Roland, Steffen; Kniepert, Juliane; Love, John A.; Negi, Vikas; Liu, Feilong; Bobbert, Peter; Melianas, Armantas; Kemerink, Martijn; Hofacker, Andreas; Neher, Dieter (The journal of physical chemistry letters, 2019)
We employed bias-assisted charge extraction techniques to investigate the transient and steady-state recombination of photogenerated charge carriers in complete devices of a disordered polymer-fullerene blend. Charge recombination is shown to be dispersive, with a significant slowdown of the recombination rate over time, consistent with the results from kinetic Monte Carlo simulations. Surprisingly, our experiments reveal little to no contributions from early time recombination of nonequilibrated charge carriers to the steady-state recombination properties. We conclude that energetic relaxation of photogenerated carriers outpaces any significant nongeminate recombination under application-relevant illumination conditions. With equilibrated charges dominating the steady-state recombination, quasi-equilibrium concepts appear suited for describing the open-circuit voltage of organic solar cells despite pronounced energetic disorder.